Persistence of a Repressed Epstein-Barr Virus Genome in Burkitt Lymphoma Cells Made Resistant to 5-Bromodeoxyuridine - Hampar, Berge (1971)
The P3HR-1 line of human lymphoblastoid cells that is Epstein-Barr virus positive was made resistant to 5-bromodeoxyuridine. Epstein-Barr virus-associated antigens, but not virus particles, were produced in P3HR-1(BU) cells maintained on 5-bromodeoxyuridine. However, virus particles did appear within 4 days after removal of the drug. Thymidine kinase activity was limited to P3HR-1(BU) cells producing viral antigen, whereas all control P3HR-1 cells showed thymidine kinase activity regardless of viral antigen synthesis. Cellular DNA in most P3HR-1(BU) cells was made via pathways that did not involve thymidine kinase. In cells having a pathway that involved thymidine kinase, a second DNA of density 1.71 g/cm(3), corresponding to Epstein-Barr virus, was detected. It was concluded that: (a) a repressed Epstein-Barr virus genome persists in P3HR-1(BU) cells that do not contain thymidine kinase, with activation of the viral genome being accompanied by productive infection and the appearance of enzyme, and (b) thymidine kinase activity in P3HR-1(BU) cells could be used as a marker for viral genome expression.